The Influence of Product Quality, Brand and Promotion on Purchase Decisions for Sports Equipment (Indonesian Athletes) - Neng Siti Komariah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was used to measure the effect of product quality, brand and promotion on purchase decisions for sports equipment for athletes in region x. This research is a quantitative study in which the object used is the athletes in area x. This research was conducted using a non-probability sampling technique with a purposive sampling method. The number of samples used in this study was 90 respondents. The design used in this research is hypothesis testing using the structural equitation model (SEM) – SmartPLS 3.0. The results of this study provide an explanation that the variables of product quality have a positive effect on the purchase decision for sports equipment for athletes in region x, and brand and promotion have thas no effect on the purchase decision for sports equipment for athletes in region x. This research has a limited object of research which is only carried out on the athletes in region x. This is used as a suggestion for future researchers. The novelty in this study combines the variables of product quality, brand and promotion on purchase decisions for sports equipment for athletes in region x.